The Iranian Dendrothripinae (Thysanoptera: Thripidae) with description of a new genus and species - Alavi, Jalil; Minaei, Kambiz; Fekrat, Lida (Zootaxa, 2014)
Iranodendrothrips kamalii gen. et sp. n. is described from northeast of Iran and the morphological relationships among the closely related genera, Dendrothrips and Filicopsothrips, are discussed. Pseudodendrothrips bhattii is reported for the first time from Iran. Illustrated keys are provided to the genera and species of Dendrothripinae from Iran.